Synthesis, Characterization and Biological Studies of Bis-{μ-2,2¢-[ethane-1,3-diyl-bis(nitrilomethylidyne)]diphenolato}dicopper(II) Using Triple Component Solvent System - Yousaf, Muhammad; Pervaiz, Muhammad; Fawad Zahoor, Ameer; Ijaz Hussain, Abdullah; Kaleem Khan Khosa, Muhammad; Ashraf, Sadia; Sagir, Muhammad; Zaman, Ashar-uz; Shehzad, Khurram (Asian Journal of Chemistry, 2012)
The bis-{μ-2,2¢-[ethane-1,3-diyl-bis(nitrilomethylidyne)]diphenolato}dicopper(II) with the molecular formula [Cu2(C16H14N2O2)2] shows the dimeric complex. Distorted square pyramidal geometry is formed in the community of CuII distinct by the two nitrogen atoms and two oxygen atoms of the [N,N´-bis-(salicylidene)-1,2-ethylene-diamine] (ligand) and one oxygen atom commencing both ligand performing as bridge between two ligand molecules, which are wraped in parallel path among each other. In toluene the tilted complex showed crystalline structure but to acquire more apparent X-ray crystallographic data a combination of three solvent (toluene, ethanol, ethyl acetate) was used. The synthesized ligand was analyzed and characterized by mass spectrometry, Fourier transform infrared spectroscopy, nuclear magnetic resonance spectroscopy while the titled compound was characterized by X-ray crystallography and FTIR. The complex and ligand were also engaged for antifungal and antibacterial activities against fungal species A. flavus, A. alternate and A. niger and against bacterial species Staphylococcus aureus, Escheria coli and Bacillus subbtilis. The results of these activities showed that the metal complex has extra antibacterial and antifungal actions than the precursor (ligand) against different culture media.